Extensive severe intraorbital arteriovenous malformations: report of a rare laser complication and successful management. (2nd January 2023) - Mataro, Ilaria; Di Franco, Livia; Cavaliere, Annachiara; Razzano, Sergio; Schonauer, Fabrizio; D'Andrea, Francesco; d'Alessio, Roberto
Abstract : Arteriovenous malformations (AVMs) are rare congenital errors of vascular morphogenesis, characterised by abnormal direct communications between arteries and veins, bypassing the normal capillary bed. Apart from the central nervous system, typical locations include the head and neck, and less frequently limbs, trunk or internal organs. AVMs of the head and neck often become clinically evident and symptomatic only in later childhood and are characterised by a history of variable growth, sometimes leading to large, deforming, pulsating masses with a propensity to massive haemorrhage. Therapeutic strategy is based on selective embolisation, surgical excision, or a combination of both. Radical surgical excision of local AVMs is the only effective treatment but it may be mutilating, especially for AVMs of the head and neck. Laser therapy represents a good option to treat the cutaneous aspects of AVMs nevertheless, its efficacy is limited. To the date, pharmacological therapy for AVMs is still on debate due to its controversial outcomes as it seems not as effective as other treatments and usually requires a longer course of application. However, pharmacological therapy could be useful in selected patients and for AVMs nonresponsive to traditional treatment, allowing them to obtain acceptable results without serious complications. This paper reports the case of a serious laser complication of extensive intraorbital AVM successfully treated by local reconstruction and topical pharmacological treatment.